2007
DOI: 10.1111/j.1365-2958.2007.05966.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel relaxase homologue is involved in chromosomal DNA processing for type IV secretion in Neisseria gonorrhoeae

Abstract: SummaryThe Neisseria gonorrhoeae type IV secretion system secretes chromosomal DNA that acts in natural transformation. To examine the mechanism of DNA processing for secretion, we made mutations in the putative relaxase gene traI and used nucleases to characterize the secreted DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
97
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 63 publications
0
97
1
Order By: Relevance
“…The ComB system is ancestrally related to the A. tumefaciens VirB/VirD4 system but lacks the Dtr proteins and T4CP substrate receptor required for DNA export (129,130,155). The GGI DNA release system is related to the Escherichia coli F plasmid transfer system and codes for Dtr, T4CP, and Mpf subunits commonly associated with conjugation machines (122,232). The ComB system is unique among known bacterial competence systems in its phylogenetic relatedness to T4SS.…”
Section: Dna Uptake and Release Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ComB system is ancestrally related to the A. tumefaciens VirB/VirD4 system but lacks the Dtr proteins and T4CP substrate receptor required for DNA export (129,130,155). The GGI DNA release system is related to the Escherichia coli F plasmid transfer system and codes for Dtr, T4CP, and Mpf subunits commonly associated with conjugation machines (122,232). The ComB system is unique among known bacterial competence systems in its phylogenetic relatedness to T4SS.…”
Section: Dna Uptake and Release Systemsmentioning
confidence: 99%
“…The relaxase domain of TraI GGI is fused to a phosphohydrolase (HD) domain, whose metal-dependent phosphohydrolase activity might also contribute in some way to the processing reaction. TraI GGI also possesses an N-terminal amphipathic helix that mediates binding to the inner membrane (232). Membrane binding, a property shared by other relaxases and accessory Dtr processing factors, might promote the engagement of the relaxase-DNA intermediate with the T4CP receptor at the membrane (see below).…”
Section: Processing For Dna Release and Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…The DNA secretion assay was performed as described previously (39). Briefly, piliated (P ϩ ) gonococcal colonies were harvested from a GCB plate and grown for 2 h at 37°C with aeration in GW medium.…”
mentioning
confidence: 99%
“…Our studies have demonstrated that ϳ80% of gonococcal strains carry the genes for a type IV secretion system (T4SS) (11,21). The T4SS transports chromosomal DNA into the extracellular milieu, where the secreted DNA is effective in transforming other gonococci in the population (11,22,39). Thus, type IV secretion functions as a mechanism of DNA donation for natural transformation.…”
mentioning
confidence: 99%